Sistem Pakar Identifikasi Hama Penyakit Tanaman Sedap Malam Menggunakan Fuzzy Analytical Hierarchy Process (F-AHP) - Christian Herlando Indra Jaya; Nurul Hidayat; Donald Sihombing (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Polianthes tuberosa is one type of ornamental plants favored by consumers and has various uses such as sown flowers, cut flowers and essential oils producing materials. As consumer demand continues to increase, many farmers cultivate it. But there are limiting factors of Polianthes tuberosa production that are pests and diseases. The limited knowledge of the community on Polianthes tuberosa pests and diseases makes the lack of understanding about the types of pests and diseases and their symptoms, so they do not know what steps should be taken to handle it. To identify which pests or diseases that attack Polianthes tuberosa quickly, it is necessary to build an expert system. One method that can be used to identify pests and diseases on Polianthes tuberosa is Fuzzy Analytical Hierarchy Process (F-AHP). The identification process is done by inserting the facts of symptoms on Polianthes tuberosa and then calculated by using F-AHP. The output of this system is the identification of pests of diseases that attack Polianthes tuberosa with recommendations of its control solutions. Based on the results of test, the method of F-AHP obtained an accuracy of 93.33%, so it can be concluded this expert system to identify pests of diseases in Polianthes tuberosa using F-AHP is able to work well.